2018
DOI: 10.1097/aog.0000000000002980
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Complement Activation in Preeclampsia

Abstract: OBJECTIVE: To evaluate whether C5b-9 concentrations in blood and urine are increased in preeclampsia with severe features. METHODS: The Complement and Preeclampsia in the Americas study is a prospective, multicenter case–control study performed at six centers in Colombia from November 2015 to July 2016. The case group included women with preeclampsia with severe features, and the control group included women who were healthy or had chronic hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 40 publications
2
35
1
Order By: Relevance
“…Finally, Lokki et al noted that areas of C3b deposition were positively correlated with C1q and negatively with Factor H, a regulatory factor of the alternative pathway (147). The over-activation of the complement system in EOPE is reinforced by the rise in the plasma concentration of C5b-9, which is indicative of terminal activation (148). C-reactive proteins of the system, specifically, C3a, have also been found circulating in high concentration within the amniotic fluid in EOPE (149).…”
Section: The Dysregulation and Over-activation Of The Complement Systmentioning
confidence: 99%
“…Finally, Lokki et al noted that areas of C3b deposition were positively correlated with C1q and negatively with Factor H, a regulatory factor of the alternative pathway (147). The over-activation of the complement system in EOPE is reinforced by the rise in the plasma concentration of C5b-9, which is indicative of terminal activation (148). C-reactive proteins of the system, specifically, C3a, have also been found circulating in high concentration within the amniotic fluid in EOPE (149).…”
Section: The Dysregulation and Over-activation Of The Complement Systmentioning
confidence: 99%
“…Complement activation is associated with renal dysfunction, and there is an accumulation of markers of complement activation, such as C4d and C1q in PE; hence, the inhibition of complement activation may be helpful in controlling the renal manifestations of PE [ 121 ]. Increased urinary C5b-9 levels in PE women were found to be potential biomarkers that distinguish PE from other hypertensive disorders [ 122 , 123 ]. A study on the HTR-8/SVneo cell line showed C5a induced higher levels of sFlt-1 transcription [ 124 ].…”
Section: Pathogenesis Of Preeclampsiamentioning
confidence: 99%
“…There is precedent for complement involvement in preeclampsia pathophysiology. Other authors have noted an association between early-onset/severe preeclampsia and complement function [64][65][66] . Our observations suggest that it may be possible to identify a sub-category of cases of preeclampsia with a dominant complement-associated phenotype at the end of the first trimester.…”
Section: Characteristics Of the Proteins Differentially Associated Wimentioning
confidence: 89%